Household automatic clothes dryer with temperature control - Misbahul Jannah; Kartika Kartika; Mukhlis Mukhlis; Muthmainnah Muthmainnah; Arnawan Hasibuan; Widyana Verawaty Siregar; Rizky Almunadiansyah; Armen Abta; Asran Asran (Bulletin of Electrical Engineering and Informatics, 2026)
Problems arising from the impact of irregular weather changes on the process of drying clothes, especially jeans, are an obstacle for housewives. Commercial clothes dryers are expensive and can cause fabric damage. Cleanliness and dryness of clothes play a vital role in everyday life. This article offers a solution in the form of an automatic clothes dryer with a temperature controller using the Arduino Uno microcontroller. This tool has a humidity sensor, LCD screen, indicator light, heater, fan, and DC motor. When the humidity is high, the tool automatically activates the heater, fan, and red indicator light. After the drying process is complete, the green indicator light turns on, indicating that the clothes are dry. This study aims to develop other similar research by designing a clothes dryer control system based on Arduino Uno. Experiments show that this dryer is more efficient, taking 80 minutes compared to 240 minutes of manual drying in the sun. The humidity setting at 20 HR is the set point to ensure an optimal drying process. The contribution of this research lies in the development of efficient clothes dryer technology that can be implemented practically.